(untitled) (SCIÉNDO INGENIUM, 2022)
Currently, thanks to Mixed Reality (MR), a wide range of new applications is being generated, which mix the real world that surrounds us with a virtual world generated by a computer. The main objective of this paradigm is to immerse the user in a new environment, which is the product of the aforementioned fusion, and which we call mixed reality environment (AmMR). To achieve this immersion it is vitally important to know the location of the user (s) (especially when you want to work on tasks that require collaboration between them), and there are still no studies where the location for more than one user is explored in these environments. , is that the present work has as objective the design of an architecture, for this ATAM (Architecture Tradeoff Analysis Method) was used, which allowed the capture of the quality attribute scenarios and the evaluation of this; Likewise, it was verified that the scenarios were covered by the proposed architecture, obtaining a minimum location time of 0.10 seconds and a maximum of 0.33 seconds, generating alerts if necessary in less than one second.